FOOD AND FEEDING HABITS OF OTOLITHES RUBER (SCHNEIDER) AT CALICUT - Nair, K V Somasekharan (Indian Journal of Fisheries, 2011)
The food and feeding habits of Otolitlies ruber from the inshore fishing grounds off Calicut were studied. No regular periodicity in feeding was observed. The young ones feed mainly at the surface on Acetes and mysiids, while the adult fish feeds at the bottom chiefly on prawns and teleo&ts. The variations in the food composition rre discussed in relation to diff’erent size groups, seasons and environmental biota.